Communication Network Patterns for Villagers in Distributing Direct Cash Aid Programs during a Pandemic - Kiki Anggia Wahyuni; Ainur Rochmaniah (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the pattern of communication networks between actors in the Direct Cash Assistance Program in Karang Rejo Village. This program has been re-emerged since the entry of the Covid-19 pandemic in Indonesia and then also instructed the regional and village governments, with the aim of helping the economy of residents who are affected by the pandemic. The research method used is descriptive quantitative with communication network analysis techniques. The population is the community who receive BLT assistance from Karang Rejo Village. Random sampling technique was used for sampling, and data collection using questionnaires and unstructured interviews. The data analysis technique uses communication network techniques with the help of the UCINET application. The results of the study conclude as follows, namely (a) the Cash Direct Assistance Program uses a wheel communication network structure and a network of all channels, (b) Found roles in the communication network, namely opinion leaders, bridges, and gatekeepers (c) There are 5 clicks that occur in each opinion leader (d) Found 3 types of innovation adopters from the results of field research, namely innovators, early adopters, and early majority, (e) there are 14 opinion leaders who have influence to disseminate information.